Chlorhexidine Showers are Associated With a Reduction in Surgical Site Infection Following Spine Surgery: An Analysis of 4266 Consecutive Surgeries. Issue 6 (22nd December 2018) - Chan, Andrew K; Ammanuel, Simon G; Chan, Alvin Y; Oh, Taemin; Skrehot, Henry C; Edwards, Caleb S; Kondapavulur, Sravani; Miller, Catherine A; Nichols, Amy D; Liu, Catherine; Dhall, Sanjay S; Clark, Aaron J; et al.
Abstract: BACKGROUND: Surgical site infection (SSI) is a common complication following spinal surgery. Prevention is critical to maintaining safe patient care and reducing additional costs associated with treatment. OBJECTIVE: To determine the efficacy of preoperative chlorhexidine (CHG) showers on SSI rates following fusion and nonfusion spine surgery. METHODS: A mandatory preoperative CHG shower protocol was implemented at our institution in November 2013. A cohort comparison of 4266 consecutive patients assessed differences in SSI rates for the pre- and postimplementation periods. Subgroup analysis was performed on the type of spinal surgery (eg, fusion vs nonfusion). Data represent all spine surgeries performed between April 2012 and April 2016. RESULTS: The overall mean SSI rate was 0.4%. There was no significant difference between the pre- (0.7%) and postimplementation periods (0.2%; P = .08). Subgroup analysis stratified by procedure type showed that the SSI rate for the nonfusion patients was significantly lower in the post- (0.1%) than the preimplementation group (0.7%; P = .02). There was no significant difference between SSI rates for the pre- (0.8%) and postimplementation groups (0.3%) for the fusion cohort ( P = .21). In multivariate analysis, the implementation of preoperative CHG showers were associated with significantly decreased odds of SSI (odds ratio = 0.15, 95% confidence interval [0.03-0.55], P < .01). CONCLUSION: This is the largest study investigating the efficacy of preoperative CHG showers on SSI following spinal surgery. In adjusted multivariate analysis, CHG showering was associated with a significant decrease in SSI following spinal surgery.